Effects of Pinocembrin Pretreatment on Connexin 43 (Cx43) Protein Expression After Rat Myocardial Ischemia-Reperfusion and Cardiac Arrhythmia - Zhang, Peng (Med Sci Monit, 2018)
BACKGROUND: Cardiac infarction frequently leads to arrhythmia and ischemia/reperfusion (I/R) aggravates cardiac injury. Pinocembrin can resist cerebral ischemia and decrease cardiac infarction area. This study thus generated a rat myocardial I/R model to assess the effect on ventricular rhythm and expression of gap junction connexin (Cx43). MATERIAL/METHODS: Male SD rats were randomly assigned into sham, model, and pinocembrin (30 mg/kg) pretreatment groups (N=15 each). The I/R model was generated by ligation of the left anterior descending coronary artery for 30 min. The pinocembrin group received intravenous injection 10 min before surgery. Heart rate (HR), mean artery pressure (MAP), rate pressure product (RPP), and arrhythmia were observed at 10 min before ischemia, 30 min after ischemia, and at 30, 60, and 120 min after reperfusion. ELISA was used to assess serum CK-MB and cTnI levels. Na(+)-K(+)ATPase and Ca(+)-Mg(2+)ATPase levels were quantified by spectrometry, followed by HE staining, IHC approach for Cx43 expression, and Western blot for Kir2.1 protein expression. RESULTS: Model rats had significantly lower HR, MAP, and RPP than in the sham group, and the pinocembrin pretreatment group had higher serum indexes. Arrhythmia index, CK-MB, and cTnI were higher in the model and pinocembrin groups, while Na(+)-K(+)ATPase, Ca(+)-Mg(2+)ATPase, Cx43, and Kir2.1 proteins were lower (p<0.05). CONCLUSIONS: Pinocembrin alleviated ventricular arrhythmia in I/R rats via enhancing Na(+)-K(+)ATPase and Ca(+)-Mg(2+)ATPase activity and upregulating Cx43 and Kir2.1 protein expression.